Studi Kelayakan Bisnis Pada PT Digicon Asia Kencana - Linda Okstiana; N.Lara Santi; Dwi Astuti (CV. ITTC INDONESIA, 2025)
Business feasibility analysis is a planned process that aims to evaluate in depth a business or business to be run. The results of this analysis provide a decision on whether the business is feasible. In facing business challenges, tax consultants are here as a solution. They have in-depth expertise in tax law, experience in the application of tax regulations, and an understanding of various tax planning strategies to optimize tax liabilities and minimize unnecessary tax risks. PT Digicon Asia Kencana is a company engaged in accounting, auditing, and taxation services, with a shareholder structure that includes a main commissioner, main director, commissioners, and directors. Based on the report, PT Digicon Asia Kencana has fulfilled the legality aspect without causing environmental impacts, as well as getting support from the surrounding community. Therefore, this company is considered worthy of being a business because of its complete legality, which is an attraction for investors to invest in the company.